2016
DOI: 10.1186/s12263-016-0519-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency modulates iron metabolism independent of hemojuvelin (Hfe2) and bone morphogenetic protein 6 (Bmp6) transcript levels

Abstract: BackgroundConsidering that vitamin A deficiency modulates hepcidin expression and consequently affects iron metabolism, we evaluated the effect of vitamin A deficiency in the expression of genes involved in the hemojuvelin (HJV)-bone morphogenetic protein 6 (BMP6)-small mothers against decapentaplegic protein (SMAD) signaling pathway.MethodsMale Wistar rats were treated: control AIN-93G diet (CT), vitamin A-deficient diet (VAD), iron-deficient diet (FeD), vitamin A- and iron-deficient diet (VAFeD), or 12 mg al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…In contrast, Da Cunha et al [37] found that VAD rats had a lower hepatic HAMP mRNA levels to half those of the control levels and suggested that VAD modulates iron metabolism via ineffective erythropoiesis by down-regulated renal Epo mRNA and up-regulated Hmox1 in the spleen [37]. By using the same protocol in rats, Ribeiro Mendez et al [38] found that VAD up-regulated hepatic Bmp6 and Hfe mRNA levels and down-regulated hepatic HAMP mRNA levels, impairing HJV-BMP6-SMAD signaling pathway that normally activates the expression of hepcidin in ID. Differences in the results between these two studies may be due in part to the rats’ diet treatment, as well as the baseline levels of VA stored in their livers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Da Cunha et al [37] found that VAD rats had a lower hepatic HAMP mRNA levels to half those of the control levels and suggested that VAD modulates iron metabolism via ineffective erythropoiesis by down-regulated renal Epo mRNA and up-regulated Hmox1 in the spleen [37]. By using the same protocol in rats, Ribeiro Mendez et al [38] found that VAD up-regulated hepatic Bmp6 and Hfe mRNA levels and down-regulated hepatic HAMP mRNA levels, impairing HJV-BMP6-SMAD signaling pathway that normally activates the expression of hepcidin in ID. Differences in the results between these two studies may be due in part to the rats’ diet treatment, as well as the baseline levels of VA stored in their livers.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing of EIF2A resulted in multiple transcript variants, and affected protein translation and played a deleterious role in aging process 41 , 42 . BMP6 regulated biological processes including iron homeostasis, fat and bone development 43 , 44 . LRP1 was involved in several cellular processes and was decreased in aging 45 .…”
Section: Discussionmentioning
confidence: 99%
“…A 50% energy restriction in sheep during the third trimester of pregnancy causes a decrease in mitochondrial function in muscle fibers in adult offspring, as evidenced by the reduction of mitochondrial VO 2max , a lower respiratory coupling ratio, and an increase in the expression of PGC-1α [ 50 ]. In pigs, an energy-restrictive diet during pregnancy (approximately 13% restriction) decreased mtDNA in fetal skeletal muscle, as well as diminished the expression of PGC-1α, sirtuin 1 (SIRT1), NRF-1α (Nuclear Respiration Factor-1α), TFAM, and the β subunit of mitochondrial ATP synthase, when compared with fetuses of mothers with a standard diet during pregnancy [ 51 ].…”
Section: Nutrients Involved In Mitochondrial Function During Pregnmentioning
confidence: 99%